EPCT-02. A Phase 1 Study of Mebendazole with Bevacizumab and Irinotecan in High Grade Gliomas. (3rd June 2022) - Krystal, Julie; Hanson, Derek; Donnelly, Danielle; Atlas, Mark
Abstract: BACKGROUND: High grade gliomas (HGG) have a dismal prognosis despite multimodal therapy. Mebendazole (MBZ) is an anti-helminthic benzimidazole. In vitro, MBZ has efficacy in numerous cancer models and is able to cross the blood brain barrier. We conducted a phase 1 trial (NCT01837862) to evaluate the safety of MBZ in combination with bevacizumab (BVCZ) and irinotecan (CPT-11). OBJECTIVE: To determine the maximally tolerated dose of MBZ when given in combination with BVCZ and CPT-11 in children with high-grade gliomas; to describe the progression-free survival (PFS) and overall survival (OS) for this group. METHODS: Patients between 1 and 21 years of age with HGG were enrolled in a 3 + 3 design to escalating doses of MBZ in combination with BVCZ 10mg/kg/dose and CPT-11 150mg/m2/dose. Subjects were eligible upfront after completion of radiation or at the time of progression. MBZ was taken orally twice per day continuously and BVCZ and CPT-11 were given intravenously on days 1 and 15 of 28-day cycles. RESULTS: Between 2015 and 2020, 10 subjects were enrolled at MBZ 50mg/kg/day (n=3), 100mg/kg/day (n=4), and 200mg/kg/day (n=3). One subject assigned to 100mg/kg/day was not evaluable. Seven subjects had a diagnosis of diffuse midline glioma, 1 subject had anaplastic astrocytoma, and 1 subject had a spinal HGG. All subjects received radiation. There were no dose limiting toxicities. The most frequent G3/G4 adverse events were neutropenia (n=3), and lymphopenia (n= 4). The overall response rate was 33% with 2 subjects achieving a partial response and 1 subject achieving a complete response sustained for 10 months. The PFS and OS from the start of study treatment were 4.7 months and 11.4 months, respectively. CONCLUSION: MBZ was safe and well tolerated when administered with BVCZ and CPT-11 at doses up to 200mg/kg/day. Further studies are needed to determine the efficacy of this treatment.